Intervención del terapista respiratorio en paciente femenino de 60 años con enfermedad pulmonar obstructiva crónica. - Gómez Damiani, Karen Estefanía (2023)
Chronic obstructive pulmonary disease is a pathology with a high prevalence of morbidity and mortality worldwide due to intrapulmonary and extrapulmonary involvement, the clinical case of the patient, a 60-year-old woman was diagnosed with COPD and was hospitalized with symptoms of characteristic weakness, difficulty breathing with light exertion and sweating. Hours of evolution plus tachypnoea, tachycardia, intercostal contractions and saturation up to 86%. The objective of this project was to define an intervention by the respiratory disease therapist in a 60-year-old woman with chronic obstructive pulmonary disease, taking into account the conclusion that the physiotherapeutic measures oxygenation, ventilation and rehabilitation of the respiratory tract form a cornerstone. for the treatment of different stages of this pathology.